Cerebral Necrosis After Radiotherapy and/or Intraarterial Chemotherapy for Brain Tumors: PET and Neuropathologic Studies - Di Chiro, Giovanni; Oldfield, Edward; Wright, Donald C.; De Michele, Domenic; Katz, David A.; Patronas, Nicholas J.; Doppman, John L.; Larson, Steven M.; Ito, Masanori; Kufta, Conrad V. (American Journal of Neuroradiology, 1987)
Cerebral necrosis after radiotherapy for brain tumors is being recognized as a problem more common than previously estimated. Distinction between this iatrogenic complication and tumor recurrence cannot be made by either CT or MR imaging. By using positron emission tomography (PET) with 18F-deoxyglucose (FOG) we were able to reach a diagnosis of radiation necrosis, later verified, in 10 of 95 patients referred for the purpose of differentiating tumor recurrence from necrosis. The critical PET-FOG feature was focal hypometabolism in the area of necrosis, which contrasted with the hypermetabolism associated with the residual/recurrent tumor. In addition, four cases of cerebral necrosis after supraophthalmic, intraarterial chemotherapy (BCNU) were studied with the PET-FOG method. The area of chemotherapy damage was also characterized by marked hypometabolism. Histology revealed both similarities and differences between radio- and chemonecrosis.